Effect of Aquatic Therapy on Motor Development and Social Skills in Children with Autism Spectrum Disorder: A Systematic Review - Flores-Figueroa, José de Jesús (2026)
Objective: This systematic review examines the effects of Aquatic Therapy (AT) on Motor Development (MD) and Social Skills (SS) in children with Autism Spectrum Disorder (ASD), following PRISMA guidelines. Methods: We analyzed English-language articles published from 2018 to December 2023, including randomized controlled trials (RCTs) and other experimental studies. Using strict selection criteria, we identified five studies investigating children aged 6-12 years who participated in 1-3 weekly AT sessions over 8 to 43 weeks. Results: Findings consistently demonstrate significant improvements in Fine and Gross Motor Skills (FMS, GMS), Visual-Motor Skills (VMS), and multiple aspects of SS. These results highlight AT as a promising intervention for simultaneously enhancing motor and social functioning in children with ASD. An updated search conducted in July 2024 confirmed the relevance and specificity of these findings, reinforcing the need for further research to refine AT interventions. Conclusion: AT is a multifaceted and beneficial intervention that enhances critical developmental areas in children with ASD. Continued research is essential to optimize its therapeutic potential and maximize long-term developmental outcomes.